Examination of Borax in Meatballs: Qualitative Analysis - Yunitasari, Norainny; Dalmayanti, Fanny; Ratnasari, Diah (Journal of Food and Pharmaceutical Sciences, 2025)
Borax is a chemical that is hazardous to health and is often misused as a food additive. The addition of this chemical is to make food chewier and more durable. It is important to test the presence of borax in snacks around us. The purpose of this study was to test the presence of borax in meatballs sold in the town square in one of the cities in East Java. The test method was carried out qualitatively, namely organoleptic test, AgNO3 test, turmeric extract test, and borax test kit. The results showed that all meatball samples tested positive for borax. Organoleptically, meatballs containing preservatives do not easily become soft (remain chewy), do not give off a bad smell for longer, and do not grow mold easily. This kind of research is important to anticipate the emergence of diseases due to borax abuse.